Human Monocytic U937 Cells Kill Salmonella In Vitro by NO-Independent Mechanisms - Ekman, Päivi (American Society for Microbiology, 1999)
Nitric oxide (NO) has a central role in host defense against intracellular microbes. HLA-B27 has been shown to directly modulate host-microbe interaction in vitro, leading to the impaired elimination of Salmonella in human monocytic U937 cells. Here, we studied whether impaired elimination of Salmonella would result from differences in NO production between HLA-B27- and HLA-A2-transfected U937 cells. Both human monocytic transfectants produced NO equally well and killed Salmonella via NO-independent mechanisms.